(untitled) (The University of Nairobi Journal of Language and Linguistics, 2023)
The aim of this paper was to investigate the Kimeru-influenced misspellings and wrong lexical choices in the Kiswahili compositions of three schools in the Meru County of Kenya, with gender as a variable. The objectives were to establish which word categories were most involved in the said misspellings and wrong lexical choices and to establish whether gender was a determining factor in producing such language errors. A total sample of 90 students, selected through stratified random sampling from three schools (i.e. a sub-sample of 30 from each) was used. The 90 participants were required to write a composition. In relation to misspellings, the results show that quite a number of Kiswahili words were written the same way they would be pronounced in Kimeru, while in relation to the wrong lexical choices, verbs were the most borrowed category (at a rate 62%), with various other word categories sharing the remaining 38%. It also emerged that the male students made significantly more wrong lexical choices than the female ones (62% vs. 38).